Longitudinal Flow Decorrelations in Xe + Xe Collisions at √sNN = 5.44 TeV with the ATLAS Detector - Alonso, Francisco (2021)
The first measurement of longitudinal decorrelations of harmonic flow amplitudes vn for n = 2-4 in Xe + Xe collisions at √sNN = 5.44  TeV is obtained using 3  μb⁻¹ of data with the ATLAS detector at the LHC. The decorrelation signal for v₃ and v₄ is found to be nearly independent of collision centrality and transverse momentum (pT) requirements on final-state particles, but for v₂ a strong centrality and pT dependence is seen. When compared with the results from Pb + Pb collisions at √sNN = 5.02  TeV, the longitudinal decorrelation signal in midcentral Xe + Xe collisions is found to be larger for v₂, but smaller for v₃. Current hydrodynamic models reproduce the ratios of the vn measured in Xe + Xe collisions to those in Pb + Pb collisions but fail to describe the magnitudes and trends of the ratios of longitudinal flow decorrelations between Xe + Xe and Pb + Pb. The results on the system-size dependence provide new insights and an important lever arm to separate effects of the longitudinal structure of the initial state from other early and late time effects in heavy-ion collisions.